Perfectionism, coping styles, and academic adjustment: Their relationships among UTAR Kampar undergraduates - Ang, See Sin; Phi, Chean Ni; Tan, Kok Wei (2021)
Undergraduates tend to face difficulty in academic adjustment since they entered into a new environment. The present study aimed to examine the relationship between adaptive perfectionism, maladaptive perfectionism, positive coping, negative coping, and UTAR Kampar undergraduates' academic adjustment. The study also investigated the prediction of perfectionism and coping styles on academic adjustment. A total of 170 participants were recruited from UTAR Kampar by using the purposive sampling method. The study adopted a cross-sectional design. Online questionnaires were used to collect data by distributing the survey across social media platforms. Short Almost Perfect Scale (SAPS), Simplified Coping Style Questionnaire (SCSQ), and Academic Adjustment Scale (AAS) were employed to assess the variables of the study. IBM SPSS Statistic (SPSS) was used to analyze the data collected. The results indicated that there was a significantly positive relationship between adaptive perfectionism and positive coping. Maladaptive perfectionism was significantly and negatively correlated with negative coping. Besides, adaptive perfectionism and positive coping were significantly and positively correlated with academic adjustment. Maladaptive perfectionism and negative coping were found to have a significantly negative relationship with academic adjustment. The findings also revealed that adaptive perfectionism and positive coping were positive predictors of academic adjustment. In contrast, maladaptive perfectionism and negative coping were negative predictors of academic adjustment. Lastly, fewer previous studies are focusing on this topic among local students. Therefore, this study can help fill in the literature gap in Malaysia context and serve as a guideline for undergraduates to have a deeper understanding of factors that influence their academic adjustment.